Aluminum metal-organic framework material for improving thermal stability of aliphatic degradable polyester as well as preparation method and application of aluminum metal-organic framework material

By preparing aluminum metal-organic frame materials under microwave conditions and blending them with aliphatic degradable polyester, the problem of insufficient thermal stability of aliphatic polyester is solved, significantly improving its thermal stability and expanding its disposable Application potential in the field of supplies.

CN119264455APending Publication Date: 2025-01-07CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411644627.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The thermal stability of aliphatic degradable polyesters is poor, resulting in a narrow processing temperature range and a reduced molecular weight, limiting their large-scale application in fields such as disposable products.

Method used

Aluminum metal-organic frame materials were prepared under microwave conditions, and [Al2(BPDC)3] was formed by mixing aluminum salt, 4,4-biphenyl acid and template benzoic acid with 1-methyl-2-pyrrolidone. NMP structure, blended with aliphatic degradable polyester as a thermal stabilizer, improves its thermal stability.

Benefits of technology

It significantly improves the initial pyrolysis temperature and maximum decomposition temperature of aliphatic degradable polyester, improves its thermal stability, and makes it more promising in the processing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005139376370000011
    Figure HDA0005139376370000011
  • Figure HDA0005139376370000012
    Figure HDA0005139376370000012
  • Figure HDA0005139376370000021
    Figure HDA0005139376370000021
Patent Text Reader

Abstract

The invention belongs to the technical field of polyester heat stabilizers, and discloses an aluminum metal-organic framework material for improving the heat stability of aliphatic degradable polyesters and a preparation method and application thereof.The preparation method comprises the steps that aluminum salt, 4, 4-diphenyldicarboxylic acid, a template benzoic acid and a 1-methyl-2-pyrrolidone solvent are mixed and subjected to a reaction under the microwave condition, and then a reaction product is obtained; the repeated structural unit of the aluminum metal-organic framework material is [Al2 (BPC) 3]. NMP, BPDC is 4, 4-biphenyl diformate anions, and NMP is 1-methyl-2-pyrrolidone; the method is simple to operate, advanced in process, short in reaction time and high in yield. The aluminum metal-organic framework material can remarkably improve the thermal stability of the aliphatic degradable polyester, the initial pyrolysis temperature T5% of the aliphatic degradable polyester can be increased by 25-35 DEG C, the maximum decomposition temperature Tmax can be increased by 25-40 DEG C, and the aluminum metal-organic framework material has a good application prospect in the field of degradable polyester processing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyester heat stabilizers, and specifically relates to an aluminum metal-organic framework material for improving the thermal stability of aliphatic degradable polyester and a microwave-assisted preparation thereof. Background Art

[0002] Aliphatic degradable polyesters, such as polylactic acid (PLA), polycaprolactone (PCL) and polydioxanone (PPDO), are a class of degradable polymer materials with excellent biocompatibility, bioabsorbability and mechanical properties. In addition to being used in surgical sutures, bone plate supports and tissue repair materials, they are also expected to be used in disposable products such as tableware, food packaging and agricultural mulch. However, this type of aliphatic degradable polyester has poor thermal stability and is prone to thermal degradation. The corresponding processing temperature range is narrow, and the molecular weight and melt viscosity will be significantly reduced due to thermal degradation during processing, which is not conducive to processing and molding. Therefore, improving the thermal stability of aliphatic degradable polyesters is of great significance for their large-scale application.

[0003] At present, there are few literature reports on improving the thermal stability of PLA, PCL and PPDO. For general polyesters, end-capping, blending, adding thermal stabilizers and other methods can be used to improve their thermal stability. Jamshidi et al. used acetic anhydride as an end-capping agent to acetylate the end groups of PLA, thereby improving the thermal stability of PLA. However, this method has limited effect on improving the thermal stability of high molecular weight polyesters and is cumbersome to operate (K. Jamshidi, S.-H. Hyon and Y. Ikada, Polymer 1988, 29, 2229-2234); Carotenuto et al. used diatomaceous earth as a filler and melt-blended it with PCL at 80°C. The addition of 15wt% of the filler can make the initial pyrolysis temperature of PCL T 5% The thermal stability of PPDO was increased by 19°C, but there were disadvantages such as large filler dosage and limited thermal stabilization effect (Maria Rosalia Carotenuto, Giuseppe Cavallaro, Ileana Chinnici, Giuseppe Lazzarand, Stefana Milioto, Molecules 2024, 29, 1203); Ding et al. used 1-phenyl-3-methyl-4-benzoyl-5-pyrazolone as a chelating agent and stirred it evenly with PPDO under a nitrogen atmosphere at 140°C. The results showed that the thermal stabilizer can improve the thermal stability of PPDO at a temperature below 230°C. The initial pyrolysis temperature of PPDO is T 5%It can be increased by 10°C (Ding Song-Dong, Wang Yu-Zhong, Polymer Degradation and Stability 2006, 91, 2465-2470). Researching and developing heat stabilizing agents with simple operation, low cost and good heat stabilization effect, and using them to enhance the heat stability of degradable polyesters has important scientific significance and application value.

[0004] Metal-organic framework materials are porous materials with periodic grid crystals formed by coordination self-assembly of metal ions and organic ligands. They have high specific surface area, good thermal stability and structural adjustability, and have been widely used in gas adsorption, catalysis, drug delivery and composite materials. In recent years, metal-organic framework materials have been used to improve the flame retardant, mechanical and corrosion resistance of polymer materials. For example, the modification of epoxy resin with P-UiO-66 can improve its flame retardant and mechanical properties. The peak heat release rate, smoke generation rate and carbon monoxide emission of the composite material are reduced by 30%, 42% and 43%, respectively, and its tensile modulus and flexural modulus are increased by 21.9% and 27.8%, respectively; ZIF-8 is used as a filler and added to epoxy resin coatings to improve the anti-corrosion performance of epoxy resin coatings, and the corrosion resistance of the coating can be increased by 70%. However, there is no literature report on the application of metal-organic framework materials to improve the thermal stability of degradable polyesters. Research and development of new metal-organic framework materials to improve the thermal stability of degradable polyesters has broad application space and also provides a new direction for research on improving the thermal properties of degradable polyesters. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] The purpose of the present invention is to provide a method for preparing aluminum metal-organic framework material by using microwaves and its application in improving the thermal stability of aliphatic degradable polyester.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A method for preparing an aluminum metal-organic framework material, comprising:

[0009] Aluminum salt, 4,4-biphenyldicarboxylic acid, template agent benzoic acid and 1-methyl-2-pyrrolidone solvent are mixed and reacted under microwave conditions, and an aluminum metal-organic framework material is obtained after filtration and separation. Its repeating structural unit is [Al2(BPDC)3]·NMP, BPDC is 4,4-biphenyldicarboxylic acid anion, and NMP is 1-methyl-2-pyrrolidone.

[0010] The microwave conditions include: microwave output power of 200-800W, microwave frequency of 2000-3000MHz; reaction conditions include: reaction temperature of 80-140°C, reaction time of 10-60 minutes.

[0011] Furthermore, the aluminum salt includes one or more of aluminum nitrate, aluminum sulfate, and aluminum chloride.

[0012] Furthermore, the molar ratio of the aluminum salt to 4,4-biphenyldicarboxylic acid is 1:2-8.

[0013] Furthermore, the molar ratio of the aluminum salt to the template agent benzoic acid is 1:0.1-2.

[0014] Furthermore, the amount of 1-methyl-2-pyrrolidone solvent corresponding to 1 mmol of aluminum salt is 5 to 50 ml.

[0015] An aluminum metal-organic framework material is prepared by the method described above.

[0016] An application of an aluminum metal-organic framework material, wherein the aluminum metal-organic framework material is applied to improve the thermal stability of aliphatic degradable polyester, comprising:

[0017] The aluminum metal-organic framework material and the aliphatic degradable polyester are first mixed in a ball mill, and then the mixture is put into a screw extruder, and is fully mixed and plasticized to obtain a polyester product.

[0018] The screw extrusion conditions include: a processing temperature of 120° C. to 200° C. and a screw speed of 5 to 30 rpm.

[0019] Furthermore, the aliphatic degradable polyester includes one of polylactic acid, polycaprolactone and polydioxanone.

[0020] Furthermore, the mass ratio of the aliphatic degradable polyester to the aluminum metal-organic framework material is 100:0.1-10, which can make the initial pyrolysis temperature of the aliphatic degradable polyester T 5% Can increase the maximum decomposition temperature T by 25-35℃ max It can increase the temperature by 25-40℃ and has good application prospects in the field of biodegradable polyester processing.

[0021] Compared with the prior art, the present invention has the following characteristics:

[0022] The aluminum metal-organic framework material of the present invention has a simple preparation method, advanced technology, short reaction time and a yield of up to 95.6%. Compared with heat stabilizers such as phosphite, calcium stearate, and antioxidant 1010, the aluminum metal-organic framework material of the present invention can significantly improve the thermal stability of aliphatic degradable polyesters and can make the initial pyrolysis temperature T 5% Can increase the maximum decomposition temperature T by 25-35℃ max It can increase the temperature by 25-40℃ and has good application prospects in the field of biodegradable polyester processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] in Figure 1 This is a schematic diagram of the infrared spectrum of the aluminum metal-organic framework material in Example 1;

[0024] in Figure 2 This is a schematic diagram of the diffraction of the aluminum metal-organic framework material powder in Example 1;

[0025] in Figure 3 This is a thermogravimetric diagram of the aluminum metal-organic framework material in Example 1;

[0026] in Figure 4 This is a schematic diagram of thermogravimetric analysis of polylactic acid modified with aluminum metal-organic framework material in Example 9;

[0027] in Figure 5 This is a schematic diagram of thermogravimetric analysis of polycaprolactone modified with aluminum metal-organic framework material in Example 14;

[0028] in Figure 6 This is a schematic diagram of the thermogravimetric analysis of polydioxanone modified with aluminum metal-organic framework material in Example 15. Specific implementation methods

[0030] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0031] Example 1

[0032] A method for preparing aluminum metal-organic framework materials using microwave method:

[0033] Aluminum nitrate (213 mg, 1 mmol), 4,4-biphenyldicarboxylic acid (968 mg, 4 mmol), template agent benzoic acid (122 mg, 1 mmol) and 1-methyl-2-pyrrolidone (30 ml) were added to a 100 ml polytetrafluoroethylene-lined reactor, and then the reactor was placed in a microwave reactor, and the microwave output power was set to 500 W, the microwave frequency was set to 2450 MHz, and the reaction temperature was set to 110°C. The reaction was terminated after 30 minutes of reaction, and the powder was filtered and dried to obtain a white powder with a yield of 95.6% (420.1 mg, based on Al).

[0034] Infrared data (KBr, cm -1 ):3438m,2673w,1687m,1607s,1543s,1428s,1384w,1182m,1129m,1006w,928w,846m,772m,663m,642m, see Figure 1 . (Instrument model: Nicolet ESP 460)

[0035] Example 2

[0036] A method for preparing aluminum metal-organic framework material by microwave method, which is different from Example 1 only in that:

[0037] The amount of 4,4-biphenyldicarboxylic acid used was 1936 mg, 8 mmol;

[0038] The microwave output power was 500 W, the microwave frequency was 2450 MHz, the reaction temperature was 140 °C, and the reaction time was 30 min;

[0039] The rest is the same as in Example 1.

[0040] The product was obtained as a white powder with a yield of 88.7% (389.4 mg, based on Al).

[0041] Example 3

[0042] A method for preparing aluminum metal-organic framework material by microwave method, which is different from Example 1 only in that:

[0043] The amount of 1-methyl-2-pyrrolidone used is 5 ml;

[0044] The microwave output power was 200 W, the microwave frequency was 2000 MHz, the reaction temperature was 80 °C, and the reaction time was 60 min;

[0045] The rest is the same as in Example 1.

[0046] The product was obtained as a white powder with a yield of 53.1% (233.4 mg, based on Al).

[0047] Example 4

[0048] A method for preparing aluminum metal-organic framework material by microwave method, which is different from Example 1 only in that:

[0049] The amount of template agent benzoic acid used was 244 mg, 2 mmol;

[0050] The microwave output power was 500 W, the microwave frequency was 2450 MHz, the reaction temperature was 110 °C, and the reaction time was 30 min;

[0051] The rest is the same as in Example 1.

[0052] The obtained product was a white powder with a yield of 80.3% (352.9 mg, based on Al).

[0053] Example 5

[0054] A method for preparing aluminum metal-organic framework material by microwave method, which is different from Example 1 only in that:

[0055] The amount of 4,4-biphenyldicarboxylic acid used is 484 mg, 2 mmol; the amount of 1-methyl-2-pyrrolidone used is 50 ml;

[0056] The microwave output power was 500 W, the microwave frequency was 2450 MHz, the reaction temperature was 110 °C, and the reaction time was 30 min;

[0057] The rest is the same as in Example 1.

[0058] The obtained product was a white powder with a yield of 67.2% (295.3 mg, based on Al).

[0059] Example 6

[0060] A method for preparing aluminum metal-organic framework material by microwave method, which is different from Example 1 only in that:

[0061] Aluminum sulfate was used to replace aluminum nitrate; the amount of template agent benzoic acid used was 12.2 mg, 0.1 mmol;

[0062] The microwave output power was 500 W, the microwave frequency was 2450 MHz, the reaction temperature was 140 °C, and the reaction time was 30 min;

[0063] The rest is the same as in Example 1.

[0064] The product was obtained as a white powder with a yield of 75.6% (332.2 mg, based on Al).

[0065] Example 7

[0066] A method for preparing aluminum metal-organic framework material by microwave method, which is different from Example 1 only in that:

[0067] Aluminum chloride is used instead of aluminum nitrate;

[0068] The microwave output power was 800 W, the microwave frequency was 3000 MHz, the reaction temperature was 110 °C, and the reaction time was 10 minutes;

[0069] The rest is the same as in Example 1.

[0070] The obtained product was a white powder with a yield of 91.7% (403.1 mg, based on Al).

[0071] Comparative Example 1: Effect of Microwave Treatment

[0072] A method for preparing aluminum metal-organic framework materials:

[0073] Aluminum nitrate (213 mg, 1 mmol), 4,4-biphenyldicarboxylic acid (968 mg, 4 mmol), template benzoic acid (122 mg, 1 mmol) and 1-methyl-2-pyrrolidone (30 ml) were added to a 100 ml polytetrafluoroethylene-lined reactor, and then the reactor was placed in an oven at a reaction temperature of 110°C. The reaction was terminated after 2 days of reaction, and the mixture was filtered and dried to obtain a white powder of aluminum metal-organic framework material with a yield of 46.5% (204.4 mg, based on Al).

[0074] Comparative Example 2

[0075] A method for preparing aluminum metal-organic framework materials:

[0076] Aluminum nitrate (213 mg, 1 mmol), 4,4-biphenyldicarboxylic acid (968 mg, 4 mmol), template benzoic acid (122 mg, 1 mmol) and 1-methyl-2-pyrrolidone (30 ml) were added to a 50 ml four-necked flask. The reaction temperature was 110°C. The reaction was terminated after mechanical stirring for 3 days. The powder was filtered and dried to obtain a white powder with a yield of 31.2% (137.1 mg, based on Al).

[0077] Comparative Example 3: Effect of template agent benzoic acid

[0078] A method for preparing aluminum metal-organic framework materials using microwave method:

[0079] Aluminum nitrate (213 mg, 1 mmol), 4,4-biphenyldicarboxylic acid (968 mg, 4 mmol) and 1-methyl-2-pyrrolidone (30 ml) were added to a 100 ml polytetrafluoroethylene-lined reactor, and then the reactor was placed in a microwave reactor, and the microwave output power was set to 500 W, the microwave frequency was set to 2450 MHz, and the reaction temperature was set to 110°C. The reaction was terminated after 30 minutes, and the mixture was filtered and dried to obtain a white powder with a yield of 23.5% (103.3 mg, based on Al).

[0080] Example 8

[0081] Characterization of the aluminum metal-organic framework material of Example 1.

[0082] (1) Phase purity characterization of aluminum metal-organic framework materials

[0083] The phase purity of aluminum metal-organic framework materials can be characterized by X-ray powder diffractometer. The diffraction pattern of aluminum metal-organic framework materials prepared by microwave method was measured by Rigaku D / Max-2500 of Japan (Cu Kα target, fixed monochromator, tube voltage 40kV, tube current 100mA, scanning rate 8° / min). The results show that aluminum metal-organic framework materials prepared by microwave method have reliable phase purity. Figure 2 : Schematic diagram of powder diffraction of aluminum metal-organic framework materials.

[0084] (2) Characterization of thermal stability of aluminum metal-organic framework materials

[0085] The thermal stability of aluminum metal-organic framework materials can be characterized by a thermogravimetric analyzer. The aluminum metal-organic framework materials prepared by microwave method were measured by a German NETZSCH / TG209F3 thermogravimetric analyzer (nitrogen atmosphere, temperature range of 50-700°C, heating rate of 10°C / min). The thermogravimetric curve shows that the coordination skeleton of aluminum metal-organic framework materials prepared by microwave method stabilizes to 287°C and then slowly loses weight to 450°C, then quickly loses weight to 610°C, and finally loses weight slowly. Figure 3 : Schematic diagram of thermogravimetric analysis of aluminum metal-organic framework materials.

[0086] Example 9

[0087] The aluminum metal-organic framework material prepared by the microwave method in Example 1 was used to study the improvement of the thermal stability of aliphatic degradable polyester.

[0088] Polylactic acid (5 g) and aluminum metal-organic framework material (0.15 g) were mixed in a ball mill for 10 minutes, and then the mixture was put into a screw extruder at a processing temperature of 140°C and a screw speed of 15 rpm. After sufficient mixing and plasticization, a polylactic acid product was obtained, and its initial pyrolysis temperature T5% The maximum decomposition temperature is 349°C. max It is 409℃.

[0089] Example 10

[0090] The aluminum metal-organic framework material prepared by microwave method in Example 1 is used to improve the thermal stability of aliphatic degradable polyester. Compared with Example 9, the only difference is that:

[0091] The amount of aluminum metal-organic framework material used was 0.005 g;

[0092] The rest is the same as Example 9.

[0093] The initial pyrolysis temperature of the obtained polylactic acid product is T 5% The maximum decomposition temperature is 341℃ and T max It is 394℃.

[0094] Embodiment 11

[0095] The aluminum metal-organic framework material prepared by microwave method in Example 1 is used to improve the thermal stability of aliphatic degradable polyester. Compared with Example 9, the only difference is that:

[0096] The amount of aluminum metal-organic framework material was 0.5 g, and the screw speed was 5 rpm;

[0097] The rest is the same as Example 9.

[0098] The initial pyrolysis temperature of the obtained polylactic acid product is T 5% The maximum decomposition temperature is 348℃ and T max It is 405℃.

[0099] Example 12

[0100] The aluminum metal-organic framework material prepared by microwave method in Example 1 is used to improve the thermal stability of aliphatic degradable polyester. Compared with Example 9, the only difference is that:

[0101] The processing temperature is 120°C;

[0102] The rest is the same as Example 9.

[0103] The initial pyrolysis temperature of the obtained polylactic acid product is T 5% The maximum decomposition temperature is 344℃. max It is 403℃.

[0104] Example 13

[0105] The aluminum metal-organic framework material prepared by microwave method in Example 1 is used to improve the thermal stability of aliphatic degradable polyester. Compared with Example 9, the only difference is that:

[0106] The processing temperature was 200 °C and the screw speed was 30 rpm;

[0107] The rest is the same as Example 9.

[0108] The initial pyrolysis temperature of the obtained polylactic acid product is T 5% The maximum decomposition temperature is 342℃ and T max is 400℃.

[0109] Embodiment 14

[0110] The aluminum metal-organic framework material prepared by microwave method in Example 1 is used to improve the thermal stability of aliphatic degradable polyester. Compared with Example 9, the only difference is that:

[0111] Using polycaprolactone to replace polylactic acid;

[0112] The rest is the same as Example 9.

[0113] The initial pyrolysis temperature of the obtained polycaprolactone product is T 5% The maximum decomposition temperature is 355℃. max It is 411℃.

[0114] Embodiment 15

[0115] The aluminum metal-organic framework material prepared by microwave method in Example 1 is used to improve the thermal stability of aliphatic degradable polyester. Compared with Example 9, the only difference is that:

[0116] Using polydioxanone to replace polylactic acid

[0117] The rest is the same as Example 9.

[0118] The initial pyrolysis temperature of the obtained polydioxanone product is T 5% The maximum decomposition temperature is 280℃. max is 330℃.

[0119] Example 16

[0120] Characterization of thermal stability of polyester products.

[0121] The thermal stability of the polyester product was characterized by a thermogravimetric analyzer, and the thermal stability of the polyester product was measured using a German NETZSCH / TG209F3 thermogravimetric analyzer (nitrogen atmosphere, temperature range 50-700°C, heating rate 10°C / min). Thermogravimetric analysis showed that aluminum metal-organic framework materials can improve the thermal stability of aliphatic degradable polyesters. Figure 4 : Schematic diagram of thermogravimetric analysis of polylactic acid modified with aluminum metal-organic framework materials; Figure 5 : Schematic diagram of thermogravimetric analysis of polycaprolactone modified with aluminum metal-organic framework materials; Figure 6: Schematic diagram of thermogravimetric analysis of poly(p-dioxanone) modified with aluminum metal-organic framework materials.

[0122] Comparative Example 4

[0123] Tris(2,4-di-tert-butylphenyl)phosphite is used to improve the thermal stability of polylactic acid, and the mixing process is the same as in Example 9.

[0124] The initial pyrolysis temperature of the obtained polylactic acid product is T 5% The maximum decomposition temperature is 320℃. max is 375℃.

[0125] Comparative Example 5

[0126] Antioxidant 1010 is used to improve the thermal stability of polylactic acid, and the mixing process is the same as Example 9.

[0127] The initial pyrolysis temperature of the obtained polylactic acid product is T 5% The maximum decomposition temperature is 324℃. max It is 385℃.

[0128] Comparative Example 6

[0129] Calcium stearate is used to improve the thermal stability of polylactic acid, and the mixing process is the same as in Example 9.

[0130] The initial pyrolysis temperature of the obtained polylactic acid product is T 5% The maximum decomposition temperature is 315℃. max It is 372℃.

[0131] Comparative Example 7

[0132] Antioxidant 1010 is used to improve the thermal stability of polycaprolactone, and the mixing process is the same as Example 14.

[0133] The initial pyrolysis temperature of the obtained polycaprolactone product is T 5% The maximum decomposition temperature is 332℃. max It is 397℃.

[0134] Comparative Example 8

[0135] Antioxidant 1010 is used to improve the thermal stability of polydioxanone, and the mixing process is the same as that of Example 15.

[0136] The initial pyrolysis temperature of the obtained polydioxanone product is T 5% The maximum decomposition temperature is 260℃. max It is 303℃.

[0137] Compare Column 9

[0138] ZIF-8 is used to improve the thermal stability of polydioxanone, and the mixing process is the same as Example 15.

[0139] The initial pyrolysis temperature of the obtained polydioxanone product is T 5% The maximum decomposition temperature is 231°C. max It is 267℃.

[0140] After using ZIF-8, it was found that it deteriorated the thermal stability of polydioxanone.

[0141] Comparative Example 10

[0142] The polylactic acid without adding a heat stabilizer was put into a screw extruder, and the mixing process was the same as in Example 9.

[0143] The initial pyrolysis temperature of the obtained polylactic acid product is T 5% The maximum decomposition temperature is 314℃ and T max It is 369℃.

[0144] Comparative Example 11

[0145] The polycaprolactone without adding heat stabilizer was put into the screw extruder, and the mixing process was the same as that in Example 9.

[0146] The initial pyrolysis temperature of the obtained polycaprolactone is T 5% The maximum decomposition temperature is 325℃. max It is 386℃.

[0147] Comparative Example 12

[0148] Polydioxanone without adding heat stabilizer was put into the screw extruder, and the mixing process was the same as that of Example 9.

[0149] The initial pyrolysis temperature of the obtained polydioxanone is T 5% The maximum decomposition temperature is 255℃. max It is 296℃.

[0150] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing an aluminum metal-organic framework material, characterized in that: The method comprises: mixing aluminum salt, 4,4-biphenyldicarboxylic acid, template agent benzoic acid and 1-methyl-2-pyrrolidone solvent, reacting under microwave conditions, and obtaining aluminum metal-organic framework material after filtering and separation, wherein the repeating structural unit is [Al2(BPDC)3]·NMP, BPDC is 4,4-biphenyldicarboxylic acid anion, and NMP is 1-methyl-2-pyrrolidone.

2. The method for preparing the aluminum metal-organic framework material according to claim 1, characterized in that: The aluminum salt includes one or more of aluminum nitrate, aluminum sulfate, and aluminum chloride.

3. The method for preparing the aluminum metal-organic framework material according to claim 1, characterized in that: The molar ratio of the aluminum salt to 4,4-biphenyldicarboxylic acid is 1:2-8.

4. The method for preparing the aluminum metal-organic framework material according to claim 1, characterized in that: The molar ratio of the aluminum salt to the template agent benzoic acid is 1:0.1-2.

5. The method for preparing the aluminum metal-organic framework material according to claim 1, characterized in that: The microwave conditions include: microwave output power of 200-800W, microwave frequency of 2000-3000MHz; the reaction conditions include: reaction temperature of 80-140°C, reaction time of 10-60 minutes.

6. An aluminum metal-organic framework material, characterized in that: It is prepared by the method according to any one of claims 1 to 5.

7. The use of the aluminum metal-organic framework material according to claim 6, characterized in that: The aluminum metal-organic framework material is used as a thermal stabilizer.

8. The use of the aluminum metal-organic framework material as claimed in claim 7, characterized in that: The process is carried out according to the following steps: the aluminum metal-organic framework material and the aliphatic degradable polyester are first mixed in a ball mill, and then the mixture is put into a screw extruder, and after being fully mixed and plasticized, a polyester product is obtained.

9. The use of the aluminum metal-organic framework material as claimed in claim 8, characterized in that: The aliphatic degradable polyester includes one of polylactic acid, polycaprolactone and polydioxanone; the screw extrusion conditions include: a processing temperature of 120° C. to 200° C. and a screw speed of 5 to 30 revolutions per minute.

10. The use of the aluminum metal-organic framework material according to claim 8, characterized in that: The mass ratio of aliphatic biodegradable polyester to aluminum metal-organic framework material is 100:0.1-1.